The state’s duty to support in Kant: Right duty and narrow duty as necessary condition for tripartite freedom - Rivera González, Juan (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This paper discusses the state’s duty to support for the poor, as presented by Kant in his Metaphysics of Right. First, it emphasizes the significance of this work within Kantian thought and the supreme concept of free choice in his system. Second, it explores the nature of this duty of support, particularly its character as duty of right and narrow duty. Consequently, it rejects the notion that it is a duty of beneficence, a benevolent duty of the sovereign, a type of social right, or a non-coercive right derived from equity. Third, it presents seven systematic arguments that justify the state´s duty to support as a necessary condition for the exercise of tripartite freedom for the poor: free choice, innate freedom, and practical freedom, arguments that are necessarily interrelated.